A study on the needle heating in polyester blend upholstery fabrics - (:unkn) unknown (INST NATL CERCETARE-DEZVOLTARE TEXTILE PIELARIE-BUCURESTI, 2013)
This paper presents an experimental study on needle heating in sewing different polyester blends of upholstery fabrics. For this purpose, three polyester blends of upholstery fabrics which have been sewn with two ply PES/PES corespun threads at three different thread counts with a three ranges of machine speed from 1 000 rpm to 3 000 rpm. Several of physical tests were carried out in both threads and fabrics. Thermal camera has been used to identify the temperatures of the needles during different time durations of the sewing process. The needle temperatures were observed between 113 and 311.2 degrees C at the end of 60 seconds of sewing process. The results revealed that needle temperature especially increases with an increase of machine speed and thread count. The highest needle temperatures were observed in all the thickest fabrics (2.23 mm) with the coarsest threads (150 tex). The most highest temperatures within the sewing machine speeds were obtained at the 3 000 rpm. Additionally, the thread structures were observed under a light microscope and showed that the upper threads have more fibrilation on the surface of the yarn than their lower threads. The overall results were also statistically analysed.
Keywords: needle heating; upholstery fabric; PES/PES corespun; thermal camera; TEMPERATURE